Future business and the role of purchasing and supply management: Opportunities for 'business-not-as-usual' PSM research. Issue 1 (January 2022) - Knight, Louise; Tate, Wendy; Carnovale, Steven; Di Mauro, Carmela; Bals, Lydia; Caniato, Federico; Gualandris, Jury; Johnsen, Thomas; Matopoulos, Aristides; Meehan, Joanne; Miemczyk, Joe; Patrucco, Andrea S.; et al.
Abstract: The raison d'être for this article is simple: traditional ways of researching, theorizing, and practicing purchasing and supply management (PSM) are no longer sufficient to 'meet the moment'. Scholars need to advance a "business-not-as-usual" footing approach to their work, if they are to make a meaningful contribution to addressing the current and future emergencies, as highlighted by recent extreme weather and the COVID-19 pandemic. Yet, what can this, or should this, mean for a field rooted in traditional business thinking? This article builds on the Journal of Purchasing and Supply Management's (JPSM) 25th Anniversary Special Issue editorial (2019); members of the JPSM's editorial team advance their unique perspectives on what "business-not-as-usual" means for PSM. Specifically, we advocate both thinking much more widely, in scope and ambition, than we currently do, and simultaneously building our ability to comprehend supply chains in a more nuanced and granular way. We explore whether the bias toward positivist work has omitted potentially interesting findings, and viewpoints. This leads to a call to re-think how we approach our work: should the key criteria always be to focus on theory development or testing? Should academics "think bigger"? Turning to specific research themes, illustrations of how our current thinking can be challenged or broadened by addressing the circular economy, and role of purchasing and innovation. Specifically, the focus on the PSM function as an intrapreneur within the larger organization, and the role of innovation and technology in PSM work. Taken together, we hope the ideas and arguments presented here will inform and inspire ambitious and novel approaches to PSM research with significant and enduring impact on the transformation of business.